EARLY DETECTION OF HEART FAILURE RISK IN PATIENTS WITH DIABETES - Barakayeva Nigina O’tkir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores strategies for the early detection of heart failure (HF) risk in patients with diabetes. Diabetes significantly increases the incidence of HF due to metabolic, vascular, and structural cardiac changes. Early identification of atrisk individuals allows timely intervention and prevents progression to symptomatic heart failure. The study reviews the use of biomarkers, imaging techniques, and functional assessments, highlighting their diagnostic value and clinical relevance in diabetic patients.